(untitled) (THE IRAQI JOURNAL FOR MECHANICAL AND MATERIALS ENGINEERING, 2021)
The degradation of waste plastics in the environment is such an essential issue for Earth protection. This study indicated the importance of using waste bottles to produce recycled depolymerization Polyethylene Terephthalate (DPET). The bubble column reactor technique and its effect in the depolymerization process have been investigated. The DPET with Poly-methyl methacrylate (PMMA) has been used to fabricate the hybrid polymer to improve the mechanical properties. Thus, different percentages (1, 2, 3, 5, and 10 %) of (DPET) are used to surmise its repercussions on the mechanical properties of the polymer. These ramifications were studied through a sequence of research laboratory tests, including tensile strength, Charpy impact, and shore-D hardness, and Fourier Transform Infrared Spectroscopy (FTIR) analysis. The results show a development interest, especially for impact strength and surface hardness, where both tests show compatible results, especially at (10%) of DPET. At the same time, maximum results of tensile strength are at (3%). FTIR analysis shows a chemical reaction between DPET and PMMA, which significantly improves the characteristics and makes it a wide range of available applications.